Epitranus longicaudatus: A new species of chalcidid wasps (Hymenoptera: Chalcididae, Epitraninae) from southern India - C. Binoy; S. Santhosh; M. Nasser (Journal of Insect Biodiversity and Systematics, 2024)
A new species, Epitranus longicaudatus sp. nov., is described with illustrations from South India, expanding the genus Epitranus Walker to 73 species globally and 18 from India. The new species is compared with the congeneric species E. salinae Narendran, originally described from Malaysia. Both E. longicaudatus sp. nov. and E. salinae are easily identified within the monotypic subfamily in having large metasoma, more than twice as long as petiole and having gastral terga following the first, telescopic and retracted beneath the first. E. salinae is also diagnosed and illustrated using digital images for the first time. These two species complex is the largest of all described Epitranus.